Romiplostim for the Emergency Management of Severe Immune Thrombocytopenia with Intracerebral Hemorrhage - Gellens, Romain; Habchi, Sabrina; Freppel, Sebastien; Couret, David; Iacobelli, Silvia (Frontiers in Neurology, 2018)
Currently, we lack well-established guidelines for the emergency management of severe immune thrombocytopenia (ITP) with life-threatening bleeding. We now report the management of 2 patients with severe ITP, complicated by substantial cerebral hemorrhage, requiring urgent surgery due to refractory intracranial hypertension. To rapidly boost platelet counts, corticosteroids, intravenous immunoglobulin, and iterative platelet transfusions were given; all were ineffectual. Romiplostim, a thrombopoietin receptor agonist, was then administered as an “on demand therapy”, with the result that a rapid and sustained increase of platelet counts was achieved, thus allowing for postoperative hemostasis. Both patients recovered good neurological condition, suggesting the potential utility of romiplostim, in combined therapy, for the emergency management of severe ITP.